Linking Emotional Intelligence to Mental Health in Chinese High School Teachers: The Mediating Role of Perceived Organizational Justice - Shen, Sha; Tang, Tianqi; Shu, Hong; Wang, Saidi; Guan, Xiangli; Yan, Xiangdong; Wang, Yanli; Qi, Yun; Feng, Rui (Frontiers in Psychology, 2022)
Compare with other professions, teachers are reported to have a higher risk of poor mental health. This study examined the relationships between emotional intelligence, perceived organizational justice, and mental health among Chinese high school teachers. Three hundred and eighty-one high school teachers, with their age range between 21 and 50 years, were administered the Emotional Intelligence Scale, Perceived Organizational Justice Scale, and Mental Health Scale. The result found that emotional intelligence and perceived organizational justice directly influence the mental health of high school teachers. In addition, perceived organizational justice mediated the association between emotional intelligence and mental health. Moreover, the present study analyzes the different role of subtypes of perceived organizational justice on the relationships between emotional intelligence and mental health, and the results showed that the mediating effects of perceived distributive justice and interactive justice on emotional intelligence and mental health are not significant, only the perceived procedural justice mediated the relationships between emotional intelligence and teachers’ mental health. The results are discussed in a conceptual context.